Motivation :biological, psychological, and environmental - Deckers, Lambert (New york, 2014)
Well-grounded in the history of the field, the fourth edition of Motivation: Biological, Psychological, and Environmental combines classic studies with current research. The text provides an overarching organizational scheme of how motivation (the inducement of action, feelings, and thought) leads to behavior from physiological, psychological, and environmental sources. The material draws on topics that are familiar to students while maintaining a conversational tone to sustain student interest.